Learning compassionate care: Experiences of nursing students. (May 2021) - Su, Jing Jing; Paguio, Jenniffer Torralba; Masika, Golden Mwakibo; Wang, Mian; Redding, Sharon R.
Abstract: Compassion is a core value of the nursing profession which enables nurses to empathize with and help alleviate patient suffering. Literature increasingly reports a lack of compassion in patient care by students and junior nurses; empirical knowledge regarding experiences of compassionate care among nursing students remains understudied. Student experiences in the clinical setting may influence their development of compassion competencies. This study explored the experiences of baccalaureate nursing students in gaining competencies to deliver compassionate care during their clinical practice year. A descriptive qualitative study using semi-structured in-depth interviews was conducted. Thematic analysis was employed, generating six themes. The first three themes depict positive aspects of compassion development, including 'gaining patient acceptance, ' 'motivation for professional growth, ' and 'establishing an emotional bond with patients.' On the other hand, the other three themes capture the barriers to compassionate care, 'distrust, ' 'fear of harm due to violence, ' and 'heavy workload.' The positive and negative experiences shared by students indicate that hospital and nursing administrators need to foster a positive practice environment and nursing instructors should become role models to encourage compassionate care. Highlights: Providing compassionate care helps nursing students to gain acceptance by patients and be motivated for professional growth. Students' experiences of distrust, violence and heavy workload from patients and instructors hinder compassionate care. Hospital and nursing administrators need to foster a positive practice environment. Nursing instructors should be role models to promote compassionate care.